Syn-Eruptive Conditions of the AD 1530 Sub-Plinian Eruption of La Soufrière of Guadeloupe (Lesser Antilles) - Martel, Caroline; Pichavant, Michel; Balcone-Boissard, Hélène; Boudon, Georges (Frontiers in Earth Science, 2021)
New data on the matrices (microlites, residual glasses, and bubbles) of pumice, scoria, and dense clasts erupted during the AD 1530 andesitic eruption of La Soufrière of Guadeloupe are presented. The data include microlite phase assemblage, composition, content, and number density, residual glass composition and H2O content, and vesicularity. These analytical data are combined with published data from phase-equilibrium and kinetic experiments, in order to estimate pressures of microlite crystallization and magma ascent rates. The results suggest that the studied samples contain 5 to 40 vol% microlites, mostly nucleated in the reservoir following the intrusion of a more mafic magma. Only two samples nucleated microlites during magma ascent in the volcanic conduit. The AD 1530 eruptive sequence started with phreatomagmatic explosions tapping magmas that ascended during about one month (decompression rate of ~50 Pa/s) from the coldest parts of the reservoir (~825 °C and a 74 wt% SiO2 melt). These magmas had time to continuously crystallize microlites (~25 vol% plagioclase, orthopyroxene, clinopyroxene, magnetite, quartz, and apatite), but did not outgas likely due to sealed conditions. The flank collapse (preexisting ‘cold’ edifice) that followed the phreatomagmatic phase triggered a sub-Plinian eruption that progressively tapped the hotter main reservoir (~875 °C and 71 wt% SiO2 interstitial melt), emitting banded and homogeneous pumice. The banded pumice did not significantly outgas and mostly lack decompression-induced microlites, suggesting short ascent durations of the order of 0.5-1 day (decompression rates of 1400-4000 Pa/s). The following strombolian phase emitted dark scoria that did not significantly outgas and only crystallized rare microlites, suggesting ascent duration of the order of 2 days (decompression rates of ~550 Pa/s). The terminal lava dome growth involved fully outgassed magmas ascended during more than one month, giving time for microlite crystallization (~40 vol% plagioclase, orthopyroxene, clinopyroxene, magnetite, and cristobalite). As for future eruptions at La Soufrière volcano, the detection of any shallow new magmatic intrusion is crucial, since it could activate a system in which the conditions for flank collapse are already met, with possible consequent depressurization of the underlying magma, following a scenario similar to the AD 1530 eruption.